2019
DOI: 10.1109/twc.2018.2883940
|View full text |Cite
|
Sign up to set email alerts
|

Pilot- and CP-Aided Channel Estimation in MIMO Non-Orthogonal Multi-Carriers

Abstract: Motivated by 5G application requirements that challenge the use of orthogonal frequency division multiplexing (OFDM), non-orthogonal multi-carriers are being investigated. Unlike OFDM that takes advantage of orthogonal pilot observation, in non-orthogonal waveforms, pilots are contaminated by interference from multiple dimensions, i.e., inter-subsymbol-, inter-carrier-, and inter-antenna-interference, when multipleinput-multiple-output (MIMO) is also part of the transmission. Employing cyclic-prefix (CP) in mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…4. Adaptive Filtering of the estimated CIRs for b ≤ B blocks full subcarrier allocation, it would be recommended to use the whole x u,i sequence for channel estimation and apply iterative interference cancellation in analogous way as in [22], although, applying such an approach is beyond the scope of this paper.…”
Section: A Mimo Uw-based Lmmse Cementioning
confidence: 99%
“…4. Adaptive Filtering of the estimated CIRs for b ≤ B blocks full subcarrier allocation, it would be recommended to use the whole x u,i sequence for channel estimation and apply iterative interference cancellation in analogous way as in [22], although, applying such an approach is beyond the scope of this paper.…”
Section: A Mimo Uw-based Lmmse Cementioning
confidence: 99%
“…It can be observed that the SER performance with channel estimation is very close to the performance with perfect channel state information (denoted as estimated and perfect, respectively). An enhanced channel estimation performance of GFDM which even outperforms OFDM by up to 2.4 dB can be achieved by allocating pilots in the CP at the cost of an increased implementation complexity as shown in [40].…”
Section: B Channel Estimationmentioning
confidence: 99%
“…Employing cyclic-prefix (CP) in multi-carrier systems not only protects the signal from inter-symbol-interference but also allows circular interpretations of the channel which simplifies the estimation and equalization techniques. Nevertheless, the CP information is usually discarded at the receiver side [16].…”
Section: A R Fereydouni a Charmin* H Vahdati H Nasir Aghdammentioning
confidence: 99%